Treatment-related cardiovascular late effects and exercise training countermeasures in testicular germ cell cancer survivorship. (May 2015) - Christensen, Jesper F.; Bandak, Mikkel; Campbell, Anna; Jones, Lee W.; Højman, Pernille
Abstract Background. Treatment of testicular germ cell cancer constitutes a major success story in modern oncology. Today, the vast majority of patients are cured by a therapeutic strategy using one or more highly effective components including surgery (orchiectomy), radiotherapy and/or chemotherapy. However, the excellent cancer-specific survival comes at considerable costs, as individuals with a history of germ cell cancer experience serious long-term complications, including markedly increased risk of cardiovascular morbidities and premature cardiovascular death. The factors responsible, as well as their mode of action, are not fully understood and there is a lack of knowledge concerning optimal evidence-based long-term follow-up strategies. Results. Here, we present the growing body of evidence suggesting that germ cell cancer patients as a consequence of the different treatment components, are subjected to toxicities, which individually, and synergistically, can cause physiological impairments leading to sub-clinical or clinical cardiovascular disorders (i.e. the 'multiple-hit hypothesis'). Furthermore, we discuss the efficacy and utility of structured exercise training to ameliorate treatment-induced cardiovascular dysfunction to prevent premature onset of clinical cardiovascular disease in germ cell cancer survivors, with a view towards highlighting future directions of exercise-based survivorship research in the germ cell cancer setting. Conclusion. As exercise training may have the potential to ameliorate and/or reverse long-term cardiovascular disease sequelae in germ cell cancer survivors, a strong rationale exists for the promotion of exercise oncology research in this setting, in order to provide exercise recommendations for optimal germ cell cancer survivorship.